Kepuasan Kerja, Iklim Organisasi, Dukungan Organisasi Terhadap Turnover Intention Pada Karyawan Generasi Z - Zanuar Rilo Pambudi, Muhammad; Abadiyah, Rifdah (MES Management Journal, 2025)
This research investigates the influence of internal organizational aspects on the willingness of employees to remain or resign from their jobs. The study focuses on Generation Z workers employed in the production division of PT Rajawali Cakra Sakti. Using a quantitative survey approach, data were gathered from 150 respondents selected randomly and assessed through a Likert-type questionnaire. Data analysis employed multiple regression with the assistance of SPSS software. The results indicate that job satisfaction tends to reduce turnover intention, although the effect is not statistically significant. On the other hand, organizational climate and organizational support show clear and significant negative relationships with turnover intention. Together, the three variables explain a substantial portion of employees’ tendency to leave, underlining their relevance for human resource strategies aimed at workforce retention.